Health Rights for Indonesian Migrant Workers in Malaysia: A Legal Perspective - 1 Rizka Rizka, 2 Heru Santoso Wahito Nugroho, 3 Arief Budiono, 4 Wafda Vivid Izziyana, 5 Ayesha Hend (Indian Journal of Forensic Medicine & Toxicology, 2021)
Work is an application of the human beings’ responsibility in existing. The type of work may be chosenfreely whether it is within the country or abroad. This is a normative law research which is supported byempirical study. The normative law study is used to analyze the constitutional regulations regarding thehealth rights of the Indonesian migrant workers. Meanwhile, the empiric law study is used to analyze theimplementation of the regulations. The health right implementation of the Indonesian migrant workers inMalaysia is applies through health insurances based on the sosco regulations. The payment of the healthrights for the Indonesian migrant workers is the responsibility of the employer. The research results showthat in the aspect of health, the work agreements do not go according to the contract. The health securityof the Indonesian migrant workers in Malaysia is still not effective as it only covers accidents within theworking hours.